Profitability and meat yield traits of different fast growing Broiler Strains in winter - Sarker, M. S. K.; Islam, M.A.; Ahmed, S.U.; Alam, J. (Science Alert, 2002)
A total of 100 ISA-Vedette, 100 Arbor Acres and 1000 Hybro fast growing broiler chicks were divided in to 5 replications having 20 chicks in each, reared up to 42 days of age to select the suitable broiler strain of better profitability and meat yield traits. A total of 30 representative male and female broiler from each breed slaughtered at 42 days of age to investigate the dressing yield. ISA-Vedette was the highest in respect of body weight (1552.25 m/b) and feed intake (3105 m/b) followed by Hybro (1401.60 and 2764 m/b) and Arbor Acres (1372.48 and 2749 m/b) respectively. Production cost and profitability of ISA-Vedette, Hybro and Arbor Acres were 44.23 and 25.77, 50.01 and 20.00 and 50.41 and 19.49 Tk/kg live bird respectively. The strains were significantly for body weight, blood weight and giblet weight. Despite there was no significant difference among the strains, ISA-Vedette was the superior for dressing yield to the other strains. That ISA-Vedette is the most suitable strain in tropical environment in comparison with the other strains (Hybro and Arbor Acres).